The Effect of Smart Governance on Stunting and Food Security in South Asia - Huda, Fahmi Alamil; Junejo, Safiullah (HABITAT, 2026)
Purpose: This study aims to examine the role of smart governance in reducing stunting prevalence among children under five in South Asia, a region with the highest global rate, by addressing gaps in governance quality and development factors that influence child health outcomes. Design/Methodology/Approach: The research employs a quantitative panel time-averaging approach using annual data from 2000 to 2022 across eight South Asian countries, namely Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. It analyzes two governance indicators, regulatory quality and control of corruption, from the Worldwide Governance Indicators, and two development indicators, health expenditure per capita and internet usage, from the World Development Indicators, along with control variables, using fixed effects models, time averaging, between transformation, classical assumption tests, and robustness checks. Findings: The findings show that improvements in regulatory quality and control of corruption significantly reduce stunting prevalence by 2.06 percent and 1.36 percent, respectively, while increases in health expenditure per capita and internet usage reduce stunting by 0.065 percent and 0.08 percent. In contrast, higher anemia prevalence among pregnant women and increased CO2 emissions exacerbate stunting, whereas globalization reduces it. Originality/Value/Novelty: This study offers novelty by integrating governance quality and digital transformation within a Society 5.0 framework, emphasizing the importance of data driven governance and technological advancement in addressing complex public health challenges, and providing evidence based policy recommendations aligned with the Sustainable Development Goals, particularly SDG 2 and SDG 3, for inclusive, sustainable, and resilient health system improvements across developing regions globally, thereby ensuring long term policy effectiveness.